Avaliação da sanidade e germinação de sementes de soja da região noroeste do estado do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Soybean cultivation is economically inserted as one of the main agricultural products. However, in Brazil it is the main crop in area extension and production volume. Soybeans reached 95,434.6 thousand tons of production in the 2015/16 crop. The advance of the culture growth in the country has always been associated with the development of scientific research and the availability of new technologies to the productive sector. Propagated exclusively through seeds, its quality is highly dependent on the incidence of phytopathogenic microorganisms associated with it, which considerably affects the reduction of germinative power, besides the vigor, emergence, plant stand, and thus the productive yield of the crop. Considering the above, the objective of the present work was to evaluate the sanitary quality and analysis of the germination of different soybean cultivars produced in the northwestern region of the state of Rio Grande do Sul. The experiment was conducted at the Phytopathology Laboratory of the Federal University of Pampa - UNIPAMPA , campus Itaqui in the year 2017. A sanity and germination test was carried out on 12 soybean cultivars from the 2016/2017 harvest. In the evaluation of seed health, the incidence of fungi in the different soybean cultivars evaluated was evaluated and the results showed that there was a significant difference between cultivars and fungal incidence in most of the samples. Of the fungi detected Cercospora Kikuchii and Fusarium sp., Are considered important pathogens of the soybean crop. One of the important storage fungi was also detected, among them Penicillium sp. In relation to the germination test, of the 12 cultivars evaluated, it was verified by the data presented a significant difference, being observed that most of the cultivars maintained the germination index above 80%. The fungal presence in general was low considering numerous fungi associated with soybean seeds and the quality of the different soybean cultivars was not influenced by the fungi found in the sanity test.
Keywords: Glycine max (L.); Produção de sementes; Fungos; Seed production; Fungi; CNPQ::CIENCIAS AGRARIAS